2021
DOI: 10.3233/jad-201284
|View full text |Cite
|
Sign up to set email alerts
|

Poorer Theory of Mind in Amnestic Mild Cognitive Impairment Is Associated with Decreased Functional Connectivity in the Default Mode Network

Abstract: Background: Older adults living with amnestic mild cognitive impairment (aMCI) not only demonstrate impairments in Theory of Mind (ToM), relative to adults with non-amnestic MCI (naMCI), but are also at a higher risk of developing dementia. Objective: Our primary objective was to ascertain whether default mode network (DMN) functional connectivity was differentially associated with ToM abilities between MCI subgroups. Methods: Using functional magnetic resonance imaging, we investigated alterations in resting-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…First, Michaelian et al ( 2021 ), on a sample of 43 adults with MCI (aMCI, n = 19; naMCI, n = 24) used RMET (Baron-Cohen et al, 2001 ) to assess TOM and functional magnetic resonance imaging to investigate the alterations in resting-state functional connectivity within the default mode network (DMN). The authors discovered that the aMCI group revealed a significant association between poorer TOM performance and reduced functional connectivity between the bilateral temporal pole (TempP) and the left lateral temporal cortex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Michaelian et al ( 2021 ), on a sample of 43 adults with MCI (aMCI, n = 19; naMCI, n = 24) used RMET (Baron-Cohen et al, 2001 ) to assess TOM and functional magnetic resonance imaging to investigate the alterations in resting-state functional connectivity within the default mode network (DMN). The authors discovered that the aMCI group revealed a significant association between poorer TOM performance and reduced functional connectivity between the bilateral temporal pole (TempP) and the left lateral temporal cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Those results depend on the variety of tests used by the authors to investigate multiple domains of social cognition; in particular, out of 20 articles 19 different tests were used (see Table 2 ). This aspect is an advantage but, on the other hand, it is a limitation because it culminated in ambiguous results; for example, some studies reported lower TOM performance while investigating only the cognitive domain of TOM (Baglio et al, 2012 ; Maki et al, 2013 ; Moreau et al, 2015 ), yet there are studies that showed the same results using only affective tasks (Poletti and Bonuccelli, 2013 ; Yildirim et al, 2020 ; Eramudugolla et al, 2021 ; Michaelian et al, 2021 ; Orso et al, 2022 ). This heterogeneity in the adoption of the tests does not allow for overlapping results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, functional MRI studies suggested that aMCI and naMCI patients exhibited differences in activity and connectivity: (1) aMCI patients exhibited a decreased amplitude of low‐frequency fluctuations (ALFF) in the superior temporal gyrus, insula, precentral gyrus, lingual gyrus, and superior frontal gyrus compared with naMCI groups and controls; 13,14 (2) aMCI patients but not naMCI patients exhibited decreased regional homogeneity (ReHo) in the anterior cingulate gyrus compared with controls; 14 (3) compared with controls, aMCI patients and naMCI patients exhibited a different pattern of functional connectivity (FC) between the hippocampus and posterior cingulate cortex 15 and FC within the default mode network; 16 and (4) aMCI patients and naMCI patients exhibited different patterns of activation in temporal‐parietal regions during memory recognition compared with controls 17 . Moreover, aMCI and naMCI patients exhibited opposite associations between Theory of mind performance and FC between the bilateral temporal pole and the left lateral temporal cortex 18 …”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, aMCI and naMCI patients exhibited opposite associations between Theory of mind performance and FC between the bilateral temporal pole and the left lateral temporal cortex. 18 All the mentioned studies mainly focus on the static aspect of functional abnormalities, which assume that brain activity and connectivity are static over a whole resting-state functional MRI scan. However, evidence from both task-based fMRI studies and animal electrophysiology demonstrates that functional activity and connectivity may exhibit dynamic changes within time scales of seconds to minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation